2016
DOI: 10.1016/j.nbd.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structural flexibility of α-synuclein

Abstract: α-Synuclein is a conserved, abundantly expressed protein that is partially localized in pre-synaptic terminals in the central nervous system. The precise biological function(s) and structure of α-synuclein are under investigation. Recently, the native conformation and the presence of naturally occurring multimeric assemblies have come under debate. These are important deliberations because α-synuclein assembles into highly organized amyloid-like fibrils and non-amyloid amorphous aggregates that constitute the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 115 publications
(146 reference statements)
3
45
0
1
Order By: Relevance
“…7 (top panel) shows that the probability P 0 of finding the fibrils in the native state is larger for the Aβ 40 and Aβ 42 when compared to α -syn at any given temperature. This result is in agreement with a differential calorimetry experiment where it is observed that T m for β -amyloid fibrils is larger than α -syn fibrils [65,66]. In terms of the single fibril the Aβ 40 (PDB id: 2MVX) with two-fold symmetry is the most stable at higher temperature (thermophilic character) among the other two-fold and three-fold β -amyloids.…”
Section: Resultssupporting
confidence: 89%
“…7 (top panel) shows that the probability P 0 of finding the fibrils in the native state is larger for the Aβ 40 and Aβ 42 when compared to α -syn at any given temperature. This result is in agreement with a differential calorimetry experiment where it is observed that T m for β -amyloid fibrils is larger than α -syn fibrils [65,66]. In terms of the single fibril the Aβ 40 (PDB id: 2MVX) with two-fold symmetry is the most stable at higher temperature (thermophilic character) among the other two-fold and three-fold β -amyloids.…”
Section: Resultssupporting
confidence: 89%
“…The pathological gain of neurotoxicity related to α-Synuclein involves multiple biological processes. Initially, soluble α-Synuclein monomers form oligomers, then gradually accumulate into insoluble mature fibrils; eventually, α-Synuclein aggregates into large insoluble fibrils which is more toxic to neurons and can cause cell death and progressive motor impairment (Melki, 2015;Peelaerts et al, 2015;Mor et al, 2016;Karpowicz et al, 2019;Ma et al, 2019). The fibrillar form of α-Synuclein assemblies is capable of promoting aggregation of monomeric α-Synuclein in vitro and this phenomenon can spread across cells in a prion-like fashion in cell cultures and animal models (Karpowicz et al, 2019;Ma et al, 2019).…”
Section: α-Synuclein Plays a Central Role In The Neurodegenerative Prmentioning
confidence: 99%
“…The list of aSyn PTMs detected in the human brain has grown extensively in recent years, which highlights the physicochemical and structural flexibility of aSyn 11,12 . Some of these PTMs have been implicated in PD pathology -in particular the phosphorylation at Serine 129 (Ser129-p) and truncations of the C-terminus (CTT).…”
Section: Introductionmentioning
confidence: 99%